2017
DOI: 10.4172/2157-7420.1000294
|View full text |Cite
|
Sign up to set email alerts
|

Community Health Workers’ Knowledge, Attitudes and Practices Regarding Malaria Control and Prevention in Bamenda, Cameroon: A Community Based Study

Abstract: Background: Malaria is a major public health problem with about 3.4 billion people at risk worldwide. Community health workers (CHWs) are being used to control and prevent malaria in Cameroonian communities. This study's objectives were to assess CHWs' knowledge, attitudes and practices and the correlates of CHWs' knowledge regarding malaria prevention and control.Methods: A community based cross sectional survey involving 135 CHWs was conducted at the Bamenda Health District from March -May 2015. Data was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…The city is located 366 km (227 miles) north-west of the Cameroonian capital, Yaoundé. Bamenda is known for its cool climate and scenic hilly location (Shey et al, 2017). The city is an amalgamation of seven villages namely: Mankon, Mendakwe, Nkwen, Chomba, Mbatu, Nsongwa and Bandzah.…”
Section: Study Areamentioning
confidence: 99%
“…The city is located 366 km (227 miles) north-west of the Cameroonian capital, Yaoundé. Bamenda is known for its cool climate and scenic hilly location (Shey et al, 2017). The city is an amalgamation of seven villages namely: Mankon, Mendakwe, Nkwen, Chomba, Mbatu, Nsongwa and Bandzah.…”
Section: Study Areamentioning
confidence: 99%
“…In addition, a study in Rwanda (2016) showed that health cadres had a high knowledge scores for the definition of malaria 12 . Moreover, another study in Cameroon also showed low knowledge score about the diagnosis and symptoms of malaria 13 .…”
Section: Knowledge Of Mcw Towards Prevention and Control Of Malariamentioning
confidence: 99%
“…This study found that all MCWs had good practice towards malaria prevention and control with a low practice of compiling daily/weekly reports to the malaria program manager in PHC. Likewise, a study in Cameroon showed that malaria health cadres had good practice towards malaria prevention and control 13 . The MCW evaluation study by Kusmanto also stated that the implementation of MCW activities in of case detection and treatment by MCW was well executed, but the supervision activities from the PHC were not optimized 9 .…”
Section: Practice Of Mcw Towards Prevention and Control Of Malariamentioning
confidence: 99%
“…Health workers’ knowledge and practices regarding malaria diagnosis and national treatment guidelines is crucial [ 10 ] and closely related to many socio-economic factors [ 11 , 12 ], including the background of participants, their level of education, the type of health organization and years of experience [ 13 ].…”
Section: Introductionmentioning
confidence: 99%